Higher docosahexaenoic acid levels lower the protective impact of eicosapentaenoic acid on long-term major cardiovascular events - Le, Viet T.; Knight, Stacey; Watrous, Jeramie D.; Najhawan, Mahan; Dao, Khoi; McCubrey, Raymond O.; Bair, Tami L.; Horne, Benjamin D.; May, Heidi T.; Muhlestein, Joseph B.; Nelson, John R.; Carlquist, John F.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction Long-chain omega-3 polyunsaturated fatty acids (OM3 PUFA) are commonly used for cardiovascular disease prevention. High-dose eicosapentaenoic acid (EPA) is reported to reduce major adverse cardiovascular events (MACE); however, a combined EPA and docosahexaenoic acid (DHA) supplementation has not been proven to do so. This study aimed to evaluate the potential interaction between EPA and DHA levels on long-term MACE. Methods We studied a cohort of 987 randomly selected subjects enrolled in the INSPIRE biobank registry who underwent coronary angiography. We used rapid throughput liquid chromatography-mass spectrometry to quantify the EPA and DHA plasma levels and examined their impact unadjusted, adjusted for one another, and fully adjusted for comorbidities, EPA + DHA, and the EPA/DHA ratio on long-term (10-year) MACE (all-cause death, myocardial infarction, stroke, heart failure hospitalization). Results The average subject age was 61.5 ± 12.2 years, 57% were male, 41% were obese, 42% had severe coronary artery disease (CAD), and 311 (31.5%) had a MACE. The 10-year MACE unadjusted hazard ratio (HR) for the highest (fourth) vs. lowest (first) quartile (Q) of EPA was HR = 0.48 (95% CI: 0.35, 0.67). The adjustment for DHA changed the HR to 0.30 (CI: 0.19, 0.49), and an additional adjustment for baseline differences changed the HR to 0.36 (CI: 0.22, 0.58). Conversely, unadjusted DHA did not significantly predict MACE, but adjustment for EPA resulted in a 1.81-fold higher risk of MACE (CI: 1.14, 2.90) for Q4 vs. Q1. However, after the adjustment for baseline differences, the risk of MACE was not significant for DHA (HR = 1.37; CI: 0.85, 2.20). An EPA/DHA ratio ≥1 resulted in a lower rate of 10-year MACE outcomes (27% vs. 37%, adjusted p-value = 0.013). Conclusions Higher levels of EPA, but not DHA, are associated with a lower risk of MACE. When combined with EPA, higher DHA blunts the benefit of EPA and is associated with a higher risk of MACE in the presence of low EPA. These findings can help explain the discrepant results of EPA-only and EPA/DHA mixed clinical supplementation trials.